Analysis of Community Response to Family Hope Program Services in Buton Regency - Hadmar, Ahmad Muhardin; Madamang, Irwan (JSSH (Jurnal Sains Sosial dan Humaniora), 2025)
The Family Hope Program (PKH) service is one of the government's strategic steps in alleviating poverty. This program is designed to provide conditional social assistance to very poor families, with the hope of improving the quality of life of people in pre-prosperous conditions. This research explores the community's response to the Family Hope Program (PKH) services in Buton Regency. The research method used is quantitative research with the Smart PLS4 analysis tool. Data was collected by distributing questionnaires using Google Forms to people who knew about PKH services. Data analysis was carried out using content analysis techniques to determine patterns of community response to PKH services. The research results show variations in community responses to PKH services. The economic conditions of the community have been proven to have a significant influence on PKH services. However, other factors such as service quality, community participation, availability of resources, community perception, and program implementation are still not optimal in implementation. These findings provide insight into how PKH services can meet community needs. The implications of this research can be a basis for the government to increase the effectiveness and acceptability of programs and develop better communication strategies.